Point of Reckoning : The Fight for Racial Justice at Duke University - Segal, Theodore D., 1955- (Book collections on Project MUSE., 2021)
"Theodore D. Segal narrates the fraught and contested fight for racial justice at Duke University--which accepted its first black undergraduates in 1963--to tell both a local and national story about the challenges that historically white colleges and universities throughout the country continue to face."--